Random Interpulse Frequency and PRT Joint Agile Waveform Design Based on Whales Optimization Algorithm - Lang, Ping; Fu, Xiongjun; Dong, Jian; Yin, Junjun; Yang, Jian (IEEE transactions on aerospace and electronic systems, 2025)
Recent advancements in waveform generators have propelled the active agile waveform design as a prominent research direction for the antijamming solutions. Nevertheless, the efficient design of optimal agile waveforms with enhanced performance metrics, such as low integrated sidelobe level (ISL), remains a significant challenge. This deficiency may directly compromise radar capabilities in target detection, recognition, and antijamming. This article proposes a whale optimization algorithm (WOA)-based random interpulse frequency and pulse repetition time joint agile (RI-FPrtJA) waveform. First, the unique ambiguity function (AF) of the RI-FPrtJA waveform within a coherent processing interval is mathematically derived. Then, we theoretically formulate the WOA-based RI-FPrtJA waveform optimization design framework, integrated with a multiobjective optimization function that incorporates a weighted combination of the mutual incoherence property factor and ISL of the AF. Lastly, the simulations are carried out to verify the effectiveness of our proposed method. The qualitative and quantitative numerical simulation results demonstrate that the WOA-based optimized RI-FPrtJA waveform has better or competitive performances in terms of peak-to-sidelobe level ratio, ISL, and so on, compared to some current existing methods.